Founders of modern astronomy : from Hipparchus to Hawking - Mahanti, Subodh; Vigyan Prasar (Noida, India) (Noida : Vigyan Prasar, 2009)
Brief life and achievements of twenty eight world famous scientists who made significant contributions to the growth of astronomy.
Includes bibliographical references (p. [285]-291) and index.
Keywords: Astronomers -- Biography; Astronomy -- History